(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Objective: To evaluate the effectiveness of the educational program on nurses-midwives’ preventive measures about puerperal sepsis. Method: quasi-experimental study design carried among 60 Nurses and Midwives chosen by non-probability sample (purposive sample) at maternity hospitals. The data collected by the observation checklist Pretest and posttest after the implementation of the educational program. Data were analyzed using descriptive statistical data analysis approach of frequency, percentage, mean, mean of scores, a total of scores, range and standard deviation and inferential statistical data analysis approach T-test, multiple linear regressions, person correlation coefficient, and analysis of variance (ANOVA). Results: (35.3%) of them at age 20-29 years old, (75%) of them had secondary nursing school graduate level of education and (35%) of them had 11-15 years of services in the nursing field. there is a highly significant difference at P < 0.01 between the initial period of Pretest and posttest of the study sample preventive measures toward puerperal sepsis. The grand mean at pretest was (1.69) and at posttest (2.38). There is a statistically significant difference between years of service and preventive measures at posttest and Pretest of the educational program at (p-value > 0.05). Conclusion: there is an improvement in the nurses-midwives’ preventive measures level at the periods of tests after the implementation of the educational program.